Two-Stage Redo Aortic Arch Repair in a Patient With an Isolated Left Vertebral Artery. Issue 4 (July 2020) - Kawajiri, Hidetake; Khasawneh, Mohammad A.; Bower, Thomas C.; Bagameri, Gabor
A 47-year-old male presented with an enlarging distal aortic arch false lumen 6 months status post ascending and hemiarch replacement with antegrade endograft insertion for acute type A aortic dissection complicated by lower body malperfusion. Preoperative computed tomographic angiography showed an isolated but dominant left vertebral artery. A 2-stage open surgical repair was performed. First, the left subclavian artery was transposed on the common carotid and vertebral onto the subclavian. At the second stage, a redo total arch reconstruction was done with bypass grafts taken to the innominate and left common carotid arteries. The patient did well postoperatively.